Effect of Boron Addition on Corrosive Wear Behaviour of AISI 1040 Steel - Çevik, Engin; Sarıçam, Ferhat (Fırat University, 2021)
In this study; The corrosive wear behaviour of 1040 quality steels produced with the addition of boron in different proportions (3-15-30 ppm) was investigated. With this study, it is aimed to increase the wear resistance of steels exposed to abrasion in corrosive environment and to determine the maximum amount of boron that can be added under these conditions. In this context, 1040 grade commercial steels with different proportions of boron were subjected to corrosive wear tests under three different loads (10, 20 and 40N) in 3.5% sodium chloride (NaCl) solution to determine their corrosive wear behaviour. Subsequently, surface profilometry studies were conducted to determine volumetric losses after wear tests. Finally utilizing a scanning electron microscope images of worn surfaces for wear characteristics were determined. In the studies carried out, boron added up to 15 ppm in 1040 quality steels showed a positive effect in terms of mechanical and tribological properties, but after this rate, it had a negative effect.

Bu çalışmada; farklı oranlarda (3-15-30 ppm) bor ilavesi ile üretilen 1040 kalite ıslah çeliklerinin korozif aşınma davranışları incelenmiştir. Yapılan çalışma ile korozif ortamda aşınmaya maruz kalan çeliklerin aşınma dayanımının arttırılması ve bu şartlar altında ilave edilebilecek maksimum bor miktarının belirlenmesi amaçlanmıştır. Bu bağlamda, farklı oranlarda bor ilave edilen 1040 kalite ticari çelikler, korozif aşınma davranışlarının belirlenmesi amacıyla %3,5 sodyum klorür (NaCl) çözeltisi içerisinde, 10,20 ve 40N olmak üzere üç farklı yük altında korozif aşınma testlerine tabi tutulmuşlardır. Sonrasında aşınma sonrası hacimsel kayıpları belirlemek için yüzey profilometresi çalışmaları yapılmıştır. Son olarak aşınmış yüzey görüntüleri için taramalı elektron mikroskobundan faydalanılarak aşınma karakteristikleri belirlenmiştir. Yapılan çalışmalarda 1040 kalite çeliklerde 15 ppm’e kadar ilave edilen bor, mekanik ve tribolojik özellikler açısından pozitif etki gösterirken bu orandan sonra negatif etki göstermiştir.
1040 Kalite Çeliğin Korozif Aşınma Davranışına Farklı Oranlarda İlave Edilen Borun Etkisi
Keywords: Engineering; Mühendislik